Antecedents and Consequences of Marital Satisfaction in an Emirati Sample: A Structural Equation Model Analysis. Issue 4 (19th May 2017) - Al-Darmaki, Fatima Rashed; Ahammed, Shaima; Hassane, Sofoh H.; Seif Abdullah, Abdullah; Yaaqeib, Saad Ibrahim; Dodeen, Hamzeh
ABSTRACT: This study surveyed 1, 000 married Emirati men and women to explore a model of marital satisfaction in relation to self-esteem, satisfaction with life, gender-role attitudes, and general health (physical and psychological). The Emirati Marital Satisfaction Scale (EMSS), State Self-Esteem Scale (SSES), Satisfaction With Life Scale (SWLS), the Arabic General Health Questionnaire, and the Sex-Role Egalitarianism Scale were used. Confirmatory factor analysis (CFA) on the EMSS indicated a moderate fit of the data to one factor structure. CFA on SSES and SWLS indicated an adequate fit of the data to the four-factor solution and one factor, respectively. The structural equation model for the EMSS showed that both general health and gender-role attitudes predict marital satisfaction and that marital satisfaction seems to predict the individual's well-being as measured by life satisfaction and self-esteem. These results are discussed within the context of the United Arab Emirates culture and directions for future research are provided.